Partial‐mouth periodontal examination protocol for estimating periodontitis extent and severity in a US population. Issue 1 (14th March 2016) - Tran, Duong T.; Gay, Isabel C.; Du, Xianglin L.; Fu, Yunxin; Bebermeyer, Richard D.; Neumann, Ana S.; Streckfus, Charles F.; Chan, Wenyaw; Walji, Muhammad F.
Abstract: We have previously demonstrated that half‐mouth four‐site periodontal examination protocol performed well in estimating periodontitis prevalence. This study aimed to assess biases associated with this same protocol in estimating periodontitis extent and severity in a United States population. Periodontitis extent as determined by percentage of sites with clinical attachment loss (CAL) ≥3, and ≥5 mm and severity as determined by mean CAL were calculated for full‐mouth examination and half‐mouth four‐site protocol based on 3734 adults sampled from the National Health and Nutrition Examination Survey 2009–2010. Probing depth was excluded because of low data reliability. The comparison between full‐mouth and half‐mouth assessments was based on bias, relative bias, Wilcoxon signed‐rank test, and intra‐class correlation coefficient (ICC). For full‐mouth examination, periodontitis extent was 21.2% for CAL ≥3 mm and 6.9% for CAL ≥5 mm; periodontitis severity (mean CAL) was 1.73 mm. Half‐mouth four‐site protocol provided bias −1.2% and relative bias −5.7% for extent (CAL ≥3 mm). Corresponding numbers were −0.3% and 4.3% for extent (CAL ≥5 mm), −0.05 mm and −2.9% for severity. Although the difference between full‐mouth and half‐mouth assessments was statistically significant, ICCs between them were ≥0.96 for extent (CAL ≥3, 5 mm), and severity (mean CAL). Half‐mouth four‐site protocol performed well in estimating periodontitis extent and severity based on CAL. Therefore, this protocol should be considered for periodontitis surveillance.